Risk in the global real estate market international risk regulation, mechanism design, foreclosures, title systems and REITs - Nwogugu, Michael C. I. (Wiley finance series., 2011)
"Analysis of the effects of mortgage foreclosure laws on global economicsAmerica's sub-prime mortgage problems have had rippling effects on the economies of countries around the world, highlighting the many problems inherent in the legal infrastructures for both mortgages and the unconstitutional foreclosure process. The Global Mortgage: International Risk Regulation, Mechanism Design, and Constitutional Torts in Foreclosures, Titles Systems, and REITS reveals how these unconstitutional statues and processes affect housing prices, as well as the demand for housing and commercial real estate. Describes significant implications for risk regulation, interstate commerce, and legislation in the United States and some common law countries Addresses foreclosure statues and processes, mortgages and deeds of trust Shows how unconstitutional tax foreclosures and the mortgage foreclosure processes create information asymmetry, increased transaction and compliance costs, negative externalities, and inefficiency The Global Mortgage reveals the many and major problems inherent in the legal infrastructure for mortgages and foreclosure processes"--